Software-architectural configuration of the multifunctional audio digital signal processor module for signal mediatesting of audio devices - A. V. Gevorsky; M. S. Kostin; K. A. Boikov (Российский технологический журнал)
Objectives. The aim of this study is to develop and analyze parameters for a multifunctional audio module based on the ADAU1701 audio digital signal processor in the SigmaStudio environment. This will be used for testing audio devices in the following modes: routing of balanced and unbalanced audio channels according to the differential scheme Di-Box/R Di-Box; spatiotemporal and dynamic audio processing; three-band monochannel cross-separation with independent equalization; and correction of the frequency response of the audio channel with tracking notch auto-suppression of electro-acoustic positive feedback in a given spectral band.Methods. Visual-graphical architectural programming of audio modules in the SigmaStudio and Flowstone, as well as algorithms for real-time signal audio measurements and analysis of experimental data in the REW and Soundcard Oscilloscope are used.Results. The characteristics of the Di-Box/R Di-Box circuit were studied, in order to estimate the effect of differential signal conversion on the signal-to-noise ratio in the audio signal path. The characteristics of the reverberation and saturation submodules were established. Furthermore, the effect of equalization modes on the frequency response correction of a studio audio monitor was determined. The paper also studied the effect of an audio compressor on the dynamic range and the level of the output signal. The experimental results of the submodule for compensating the frequency response of an audio monitor using matched filtering were established, and the spectral characteristics of the submodule for automatic suppression of electro-acoustic positive feedback were obtained.Conclusions. The software architecture of a multifunctional audio module based on the ADAU1701 audio digital signal processor for testing and debugging media devices in a given spectral-dynamic and spectral-temporal ranges was designed. Balanced routing allows the effect of noise induced into the audio channel to be reduced 20-fold, thus enabling calibration of pickup audio devices. The audio signal processing submodule provides: compression response in the dynamic range from −27 to 18.6 dB with the possibility of equalization parameterization in the range of 0.04–18 kHz; reverberation response in the range from 0.5–3000 ms; audio-channel cross-division into 3 with the ability to adjust the amplitude-frequency response in the dynamic range from −30 to 30 dB. The auto-correction submodule of the amplitude-frequency response allows the dynamic nonuniformity of the amplitude-frequency response to be reduced by 40 dB. The auto-suppression submodule of electro-acoustic positive feedback provides notch formant suppression up to −100 dB with an input dynamic range from −50 to 80 dB.